Runoff and soil loss under in-situ moisture conservation in horti-pasture system of semi-arid climate - MAURYA1, RAGHAV; SUDHISHRI, SUSAMA; DASS, ANCHAL; KUSHWAHA, H.L.; SINGH, MAN; SHARMA, V.K.; AWASTHI, O.P.; PRASAD, SHIV (Journal of Soil and Water Conservation, 2025)
An experiment was conducted to evaluate the effects of different fodder crops and water conservation practices on rainfall-induced runoff, soil loss, nutrient loss and soil water storage in horti-pasture system of the bael orchard during 2019-20 and 2020-21. Results revealed that rainfall recorded during the study periods was 523.8 mm and 628.6 mm, with 19 and 20 rainy days, respectively. Runoff and soil loss were the highest in fields without crops or conservation practices, reaching 66.8 mm and 7.71 t/ha in 2019-20 and 62.4 mm and 7.74 t/ha in 2020-21, respectively. Implementing water conservation practices significantly reduced these losses by more than 50%. Among crops, sorghum exhibited the lowest nutrient losses and the highest soil water storage (383.3 mm and 424.6 mm in 2019-20 and 2020-21, respectively) under conservation practices. Conversely, no-crop fields had the lowest water retention. The results demonstrate that integrating water conservation practices reduces runoff, soil and nutrient losses while enhancing soil water storage, supporting sustainable horti-pasture management.